Strategic thinking in 3D : a guide for national security, foreign policy, and business professionals - Harrison, Ross, 1953- (Potomac Books, 2013)
Effective strategic thinking requires a clear understanding of one s external environment. Each organization has a unique environment, but as Ross Harrison explains in ""Strategic Thinking in 3D, "" any environment whether in the fields of national security, foreign policy, or business has three dimensions: systems, opponents, and groups. Systems strategy involves the challenge of creating leverage against opponents by shaping the external environments they rely on for sustaining their power. Opponents-based strategy requires analyzing a competitor s capability, motivation, and strategy, assessi